CLINICAL MANIFESTATIONS OF SECONDARY APLASIA AFTER CHEMOTHERAPY - Erzsebet Papp Zsuzsanna; Erzsebet Papp Zsuzsanna (Amaltea Medical Publishing House, 2016)
Objectives. Our aims were to highlight the clinical signs and symptoms of secondary bone marrow aplasia after intensive chemotherapy. Material and methods. We included in the study group 20 children with intensive cytostatic treatment aged between 9 months and 18 years, all the patients were hospitalized in the hemato-oncology department of the Pediatric Clinic Targu-Mures with the following diagnoses: acute lymphoblastic leukemia, Wilms tumor, acute myelogenous leukemia, Hodgkin lymphoma, non-Hodgkin lymphoma, neuroblastoma, and round small cell desmoplastic tumor. The inclusion criteria was the intensive chemotherapy, exclusion criteria was maintenance cytostatic treatment. It was made a dynamic clinical-biological observation protocol to note the clinical considerations of the aplastic periods after each cytostatic treatment. Bone marrow aplasia was certified by the neutropenia, anemia and thrombocytopenia. Results and discussions. The majority pathology in our study group was lymphoblastic acute leukemia (60%), followed by Wilms tumor, and one case of acute myelogenous leukemia, Hodgkin lymphoma, non-Hodgkin lymphoma, neuroblastoma, and round small cell desmoplastic tumor the distribution of age groups respecting literature data. All the patients were treated with international protocols, and after each cure followed the secondary bone marrow aplasia with the afferent pathologies: anemia, thrombocytopenia, mucositis, infections with different localizations, zona zoster reactivation. Conclusions. Secondary bone marrow aplasia duration and severity differ by cancer type. We observed the most severe clinical complications in the ALL and AML patients. Infectious complications have evolved with the individualized shades probably generated by immunological peculiarities.